2022
DOI: 10.3390/ma15228274
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization and Thermodynamic Analysis of Isotretinoin in Eleven Different Green Solvents at Different Temperatures

Abstract: The solubilization and thermodynamic analysis of isotretinoin (ITN) in eleven distinct green solvents, such as water, methyl alcohol (MeOH), ethyl alcohol (EtOH), 1-butyl alcohol (1-BuOH), 2-butyl alcohol (2-BuOH), ethane-1,2-diol (EG), propane-1,2-diol (PG), polyethylene glycol-400 (PEG-400), ethyl acetate (EA), Transcutol-HP (THP), and dimethyl sulfoxide (DMSO) was studied at several temperatures and a fixed atmospheric pressure. The equilibrium approach was used to measure the solubility of ITN, and the Ape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…At 25 °C, the mole fraction solubility of ITN in water, MeOH, EtOH, EG, PG, PEG-400, EA, and DMSO was determined to be 3.18 × 10 −7 , 4.43 × 10 −4 , 8.09 × 10 −4 , 6.24 × 10 −4 , 1.10 × 10 −3 , 5.58 × 10 −3 , 8.84 × 10 −3 , and 8.62 × 10 −2 , respectively. At 25 °C, the mole fraction solubility of ITN in water, MeOH, EtOH, EG, PG, PEG-400, EA, and DMSO has been reported as 3.16 × 10 −7 , 4.45 × 10 −4 , 8.06 × 10 −4 , 6.27 × 10 −4 , 1.07 × 10 −3 , 5.56 × 10 −3 , 8.82 × 10 −3 , and 8.64 × 10 −2 , respectively [ 13 ]. ITN had solubility values that were consistent with those reported in the literature in a number of environmentally friendly solvents [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At 25 °C, the mole fraction solubility of ITN in water, MeOH, EtOH, EG, PG, PEG-400, EA, and DMSO was determined to be 3.18 × 10 −7 , 4.43 × 10 −4 , 8.09 × 10 −4 , 6.24 × 10 −4 , 1.10 × 10 −3 , 5.58 × 10 −3 , 8.84 × 10 −3 , and 8.62 × 10 −2 , respectively. At 25 °C, the mole fraction solubility of ITN in water, MeOH, EtOH, EG, PG, PEG-400, EA, and DMSO has been reported as 3.16 × 10 −7 , 4.45 × 10 −4 , 8.06 × 10 −4 , 6.27 × 10 −4 , 1.07 × 10 −3 , 5.56 × 10 −3 , 8.82 × 10 −3 , and 8.64 × 10 −2 , respectively [ 13 ]. ITN had solubility values that were consistent with those reported in the literature in a number of environmentally friendly solvents [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…At 25 °C, the mole fraction solubility of ITN in water, MeOH, EtOH, EG, PG, PEG-400, EA, and DMSO has been reported as 3.16 × 10 −7 , 4.45 × 10 −4 , 8.06 × 10 −4 , 6.27 × 10 −4 , 1.07 × 10 −3 , 5.56 × 10 −3 , 8.82 × 10 −3 , and 8.64 × 10 −2 , respectively [ 13 ]. ITN had solubility values that were consistent with those reported in the literature in a number of environmentally friendly solvents [ 13 ]. These findings indicated that ITN solubility in various solvents may be determined using the current methodology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid-phase characterization of ITN before solubility determination (pure ITN) and after solubility determination (equilibrated ITN) was carried out to investigate the possibility of ITN evolving into polymorphs or solvates/hydrates. The findings of this characterization on pure and equilibrated ITN using differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and Fourier transforms infrared spectroscopy (FTIR) investigations are presented in our most recent work [33]. The FTIR, DSC, and PXRD spectra of both samples of ITN were said to be similar and to exhibit similar peak characteristics in our most recent paper [33].…”
Section: Solid-state Characterization and Experimental Solubility Dat...mentioning
confidence: 93%
“…The solubility of ITN in a few environmentally friendly solvents, such as propylene glycol (PG), polyethylene glycol-400 (PEG-400), and carbitol, has been documented at room temperature [28,31]. At temperatures ranging from 298.2 to 318.2 K and an atmospheric pressure of 101.1 kPa, we previously reported the solubility and thermodynamic data of ITN in 11 distinct green solvents, namely H2O, methanol, ethanol, 1-butanol, 2butanol, ethylene glycol, PG, PEG-400, ethyl acetate, carbitol, and DMSO [33]. The stock solution of DMSO has been utilized as a de facto standard for the storage of numerous substances and the distribution of various assays, including solubility assessment [34].…”
Section: Introductionmentioning
confidence: 99%